China-Vatican Interim Agreement: Subtle Yet Noticeable Changes in the Chinese Church - ZHANG, Guanglai (Journal of Research for Christianity in China (JRCC), 2025)
This article comments on the provisional agreement between China and the Vatican and its outcomes. The author contends that the China-Vatican provisional agreement and its achievements not only lay the groundwork for reconciliation within the local Church but also bring hope for communion and integration to other dioceses and the entire Chinese Church. Furthermore, it is bound to have far-reaching implications for China-Vatican relations, international relations, domestic church-state relations, and the significance of the local Church in China.